Epigenetic regulation in zebrafish development: the roles of polycomb group proteins in heart and pectoral fin development - Pratiksha S. Kavade; Saili S. Parab; Vincenza Capone; Daniela Carannante; Concetta Ambrosino; Lucia Altucci; Vincenzo Carafa (Epigenetics Communications)
Abstract Background Polycomb group proteins, known for their role in epigenetic gene silencing, are critical regulators of cell fate and tissue development across species. These highly conserved proteins are assembled into two multi-protein complexes: Polycomb Repressive Complex 1 and Polycomb Repressive Complex 2. Main body In zebrafish, a prominent vertebrate model, the roles of PRC1 and PRC2 have been extensively studied, particularly in the context of organogenesis. This review focuses on the emerging functions of PcG proteins in zebrafish development, with an emphasis on the involvement of PRC1 and PRC2 in the formation and differentiation of the heart and pectoral fins. By integrating findings from recent studies, we aim to provide a comprehensive overview of how PcG function contributes to the intricate processes underlying zebrafish heart and pectoral fin development. Conclusion This review highlights the zebrafish model as a powerful system for unravelling the complex roles of PcG proteins in vertebrate development.